IMPLEMENTATION OF GUIDANCE FOR PRIVATE ISLAMIC RELIGIOUS UNIVERSITIES - Sherin Destrianjasari; Waspodo Waspodo; Ahmad Zainuri; Saipul Annur (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
PTKIS is an Islamic Higher Education Institution that is fostered and developed by the Ministry of Religion of the Republic of Indonesia. This study aims to analyse the implementation in the development of Private Islamic Religious Universities (PTKIS) through the supervision control program, and coaching Kopertais region VII in Palembang.The research method used is descriptive qualitative with case study research type. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Meanwhile, data analysis techniques were carried out through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of PTKIS coaching through the Wasdalbin programme in Palembang went well. Kopertais conducts visits, coaching, and conducts evaluations within one year. The regulations given by Kopertais are followed by PTKIS as they should be. Through the supervision programme, Kopertais conducts direct and indirect supervision, as evidenced by the existence of a budget for certified lecturers, monitoring the tridharma of higher education activities that must be carried out by all lecturers in each semester, providing guidance through meetings either online (zoom meeting) or offline, making visits to PTKIS according to the agenda, lecturers who are required to provide reports to Kopertais. The report is in the form of a lecturer report, facilities and infrastructure report, PTKIS portal reports that are accessed such as EMIS and PDPT reports. In terms of control, socialisation, giving warnings if there are errors or lack of files, and taking action if PTKIS does not heed the warning. The last is coaching, where Kopertais provides guidance to personnel through career development for lecturers, scholarships for students, as well as accreditation and institutional legality.